Birth, life, and death of a dipolar supersolid - Sohmen, Maximilian; Politi, Claudia; Klaus, Lauritz; Chomaz, Lauriane; Mark, Manfred J.; Norcia, Matthew A.; Ferlaino, Francesca (Physical review letters, 2021)
In the short time since the first observation of supersolid states of ultracold dipolar atoms, substantial progress has been made in understanding the zero-temperature phase diagram and low-energy excitations of these systems. Less is known, however, about their finite-temperature properties, particularly relevant for supersolids formed by cooling through direct evaporation. Here, we explore this realm by characterizing the evaporative formation and subsequent decay of a dipolar supersolid by combining high-resolution in-trap imaging with time-of-flight observables. As our atomic system cools toward quantum degeneracy, it first undergoes a transition from thermal gas to a crystalline state with the appearance of periodic density modulation. This is followed by a transition to a supersolid state with the emergence of long-range phase coherence. Further, we explore the role of temperature in the development of the modulated state.
Gesehen am 30.07.2021